2016
DOI: 10.4085/1062-6050-51.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen Use and Sweat Production in Men and Women

Abstract: En esta sección se publican los resúmenes en español de artículos que han sido publicados por investigadoras/es de universidades costarricenses en otras revistas en el mundo, con su debida referencia al trabajo original, y con una breve explicación de dónde se realizó la investigación. Los artículos originales han sido publicados en otros idiomas; las revistas tienen consejo editorial y manejan un proceso de revisión por pares. Los resúmenes corresponden a estudios relacionados con las ciencias del ejercicio y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…An early study by Connolly and Wilcox measured skin temperature after 40 min of exercise for skin sites with and without an SPF 15 chemical sunscreen and found no significant differences between the sunscreen‐treated and control sites. A more recent study confirmed an SPF 50 chemical sunscreen did not impact the sweat secretion rate after 20 min of exercise, but found application of an SPF 50 inorganic sunscreen reduced the sweat secretion rate by 17% . Skin temperature was not measured in that study, so it was not clear whether thermal regulation was affected.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An early study by Connolly and Wilcox measured skin temperature after 40 min of exercise for skin sites with and without an SPF 15 chemical sunscreen and found no significant differences between the sunscreen‐treated and control sites. A more recent study confirmed an SPF 50 chemical sunscreen did not impact the sweat secretion rate after 20 min of exercise, but found application of an SPF 50 inorganic sunscreen reduced the sweat secretion rate by 17% . Skin temperature was not measured in that study, so it was not clear whether thermal regulation was affected.…”
Section: Discussionmentioning
confidence: 85%
“…This is not surprising, as the rate of water loss is extremely low at the skin surface and is not likely impeded further without the application of a very occlusive layer (petrolatum, for example). However, previous studies showed inconsistent results when comparing the rates of water loss or the ‘breathability’ of skin with sunscreens vs. without sunscreen during exercise . Moreover, it is not clear whether the sunscreens used in those studies were designed to be water‐resistant or were washed off by sweating.…”
Section: Introductionmentioning
confidence: 99%
“…Certain Fig. 2 Schematic detailing some of the body's major responses to exercise in the heat, from the acute responses to the chronic adaptations that occur with repeated exposures sunscreens [137,138] and deodorants [138,139] can impair both convective and evaporative heat loss more than others, while similar problems may occur when using eye-black or camouflage paint.…”
Section: Skin Blood Flowmentioning
confidence: 99%
“…Within this, it is important that soldiers do not compromise the limited skin-air contact that does exist. Certain sunscreens [ 137 , 138 ] and deodorants [ 138 , 139 ] can impair both convective and evaporative heat loss more than others, while similar problems may occur when using eye-black or camouflage paint.…”
Section: Strategies To Combat the Effects Of Heatmentioning
confidence: 99%
“…In another study, the effect of sweat‐inducing physical activities on the UV protection of water‐resistant sunscreens was assessed [42]. While these studies assessed sunscreen film efficacy upon sweating, others investigated the effect of sunscreen film on perspiring conditions, such as skin occlusion or changes in sweat evaporation, skin temperature and skin cooling [43–45]. In vivo evaluations of sunscreen behaviour on perspiring human skin are costly, time‐ and labour‐consuming, and complicated due to the intra‐ and inter‐subject biological variability, along with the difficulties in controlling sweat rate and in collection of sweat for analysis.…”
Section: Introductionmentioning
confidence: 99%